PENGARUH PENGGUNAAN MEDIA REALITA TERHADAP HASIL BELAJAR MATEMATIKA SDN 3 SINGKAWANG TENGAH - Agustine, Maulidya; Margiati, K.Y.; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn the process of studying mathematics in elementary school based on Kurikulum Tingkat Satuan Pendidikan (KTSP) book, there is a material in solving any issues related to money. The researcher, in this case, did a research SDN 3 Center Singkawang. In the process of studying material in solving any issues related to money, the teacher always teaches that, according to what is in the Kurikulum Tingkat Satuan Pendidikan (KTSP) book. The intention of this research to use real media as an instrument to help some teachers to convey a mathematics lesson. In this research, the researcher chooses a material in solving any issues related to money. In this research, the researcher using two classes, which is a control class and experiment class. Both of them get a similar test, pre-test and final test. The control class using an image media. The experiment class gets real media. The result of this research, there is a significant difference between the two using media in the control class and the experiment class.Â Keywords:Â Real Media, Mathematics Lesson, Result of Student learning